ВНЕДРЕНИЕ ТЕХНОЛОГИЙ КОНТЕКСТНОГО ОБУЧЕНИЯ В ПРОЦЕСС ПРОФЕССИОНАЛЬНОЙ ПОДГОТОВКИ БУДУЩИХ СПЕЦИАЛИСТОВ ГОСТИНИЧНОГО И РЕСТОРАННОГО ДЕЛА (World Science, 2018)
The article refers to the use of contextual learning technology in a university with the aim of forming creative, independently and productively thinking personality. It is proposed that to teach students on the basis of the meaning of the context of their future professional activity, and the training itself to build in connection with the dynamics of the development of the profession, providing a change in meanings, motives, goals, actions, objects and results that act as a means of solving the tasks of a specialist.